Effectiveness Of Nutrition-Based Socio-Scientific Issues Science Lessons In Fostering 21St Century Scientific Literacy Among Lower Secondary Students - Velamuthu, Rainee (2022)
The emerging concerns about nutrition SSIs like malnutrition, obesity, anaemia, etc give rise to a call to improve scientific literacy among students to be global citizens who can resolve nutrition issues in a fair and just manner while moving towards a safe global community. The study measured the effectiveness of nutrition-based SSI lessons in exploring and enhancing secondary school students’ 21st-century scientific literacy dimensions of (1) content knowledge (2) habits of mind (3) character and values (4) science as human endeavour and (5) metacognition and self-direction and its constructs. Two instruments were used to measure students’ content knowledge, the Nutrition Content Knowledge Test (NCKT) and the Big Ideas of Science Nutrition Test (BIOSNT. A questionnaire survey and interviews were conducted to measure the change in the dependent variables. Questionnaire on Habits of Mind (HOMQ), Questionnaire on Character and Values (CVQ),